Postoperative care and management of a patient undergoing pulmonary thromboendarterectomy with extracorporeal circulation and deep hypothermic circulatory arrest (1例深低温体外循环下行肺动脉血栓内膜剥脱术患者的术后监护管理) - LI Haishui (李海水); WANG Jingjing (王静静); SHEN Yanling (申艳玲); WANG Shupeng (王书鹏); YAO Lin (姚琳) (中西医结合护理)
This paper summarized the key points of postoperative monitoring and management of a patient undergoing pulmonary thromboendarterectomy with extracorporeal circulation and deep hypothermic circulatory arrest. Key points of monitoring and management included Hemodynamic monitoring, respiratory monitoring, continued anticoagulation and related issues. It is required to enhance the monitoring of vital signs and carry our targeted interventions, in order to improve the postoperative rehabilitation of the patient. pulmonary arterial hypertension. (本文总结1例深低温体外循环下行肺动脉血栓内膜剥脱术患者术后监测管理要点, 包括血流动力学监测、呼吸系统监护、持续抗凝的注意事项及观察要点等。通过密切的监测, 及时掌握患者的恢复情况, 并针对性实施干预, 是促进患者术后康复的重要措施。)